Microstructural, multilevel simulation of notch effect in ferritic ductile cast iron under low cycle fatigue. (September 2022) - Collini, L.; Pirondi, A.
Highlights: Triaxiality of stress influences the fatigue strength of ductile iron in the LCF regime. A multi-scale modelling approach analyses and rationalises this effect. A modified form of the Manson-Coffin-Basquin equation incorporating the triaxiality effect is derived. Abstract: Triaxiality of stress affects damage and failure of ductile metals. In mechanical components, triaxiality increases in the proximity of a notch, or, at the microstructural level, due to inclusions or voids. In this work,  the effect of triaxiality on the LCF of ductile cast iron is investigated by a multilevel approach, homogenizing the response of a microstructural model which feeds a notched specimen. Moving from micro- to macro-scale, results indicate that triaxiality shorten the fatigue life. Thus, the notch effect on fatigue life of cast iron can be explained in terms of the combined effects of microstructure and applied triaxiality.